Integrating waqf concept within the tourism sustainability framework: the stakeholders perspectives / Mohammed `Izzuddin Ismail - Ismail, Mohammed `Izzuddin (2021)
The purpose of this study is to observe the moderating effect of waqf contribution towards the economic pillar in the sustainability of the tourism industry in Malaysia. It examines the economic, socio-cultural, environmental, and transversal pillars contributing to the tourism industry's sustainability. The proposed model has assimilated pillars of tourism industry sustainability, sustainable development theory and waqf underlying model. This study empirically tested 150 respondents by using Partial Least Square – Structural Equation Modelling (PLS-SEM) method. The findings reveal that the model can explain 83% of the variance in the sustainability of the tourism industry. The result indicates that the economic, socio-cultural, environmental, and transversal pillars directly determine the sustainability of this industry. This study also found that the waqf contribution significantly moderates the economic pillar and tourism industry sustainability. Another possibility in enhancing the body of knowledge, a qualitative research design through the focus group discussion technique should be conducted to be more impactful. Future research can address an assessment of the waqf contribution programs among related parties in the tourism and waqf sector that should be carried out. Future research may also conduct in-depth studies on the role of sustainable pillars on tourism industry’s sustainability during and after global crises, such as COVID-19.